PUBLIC HEALTH PROMOTION OF THE IMPACT OF ORAL HEALTH ON THE QUALITY OF LIFE OF THE CHILDREN IN PRIMARY AND SECUNDARY SCHOOLS IN OHRID - Taushanova, Biljana; Pavlovska, Irina; Ljuljzime, Bajrami; Veljanovska, Snezana (Journal of Morphological Sciences; Vol 3 No 2 (2020): JMS, 2020)
Oral health is part of the global health of the individuals. The influence of problems with teeth and mouth has great influence on the general health. There is a need of using preventive programs in the goal of improving and providing oral health for the children population on a higher level. The objective of the study is to see the real situation of the teeth and mouth of the children in Ohrid and the influence of oral health on the quality of life. Cross-sectional study was performed on 248 respondents (children of the age from 11 to 18 years), selected on the base of randomization from the primary and secondary schools in Ohrid. They filled out the questionnaire (OHIP) and were reviewed by a dentists who noted the current state of teeth and were divided in two groups, (A and B). From 248 respondents, 56% are female and 44% are male (p>0.05). Out of 44 children who think that the life is of lesser quality, due to problems with teeth, 34.1% belong to group A, while 65.9% belong to group B. (Odds Ratio=1.147). (p<0.05) DMF index used by the dentists, denotes the average number of carious, extracted and sealed teeth. Factors: the level of education of children’s parents, postponing the visit to the dentist, although in need of it, interrupted sleep, feeling self-awareness of oral health care, dental treatment is an extra expense on the family budget, represent values that are statistically significant associated with the conclusion that the life has less quality due to problems with teeth. Keywords : quality of life, oral health, children population